Inutility of endoscopic sphincterotomy to prevent pancreatitis after biliary metal stent placement in the patients without pancreatic duct obstruction. (2nd April 2020) - Kato, Shin; Kuwatani, Masaki; Hayashi, Tsuyoshi; Eto, Kazunori; Ono, Michihiro; Ehira, Nobuyuki; Yamato, Hiroaki; Sano, Itsuki; Taya, Yoko; Onodera, Manabu; Kubo, Kimitoshi; Ihara, Hideyuki; et al.
Abstract: Background: The incidence of post-ERCP pancreatitis (PEP) has been reported to be significantly higher in patients without main pancreatic duct (MPD) obstruction who undergo transpapillary biliary metal stent (MS) placement than in those with ordinary ERCP setting. Objective: To evaluate the benefit of endoscopic sphincterotomy (ES) prior to MS placement in preventing PEP in patients with distal malignant biliary obstruction (MBO) without MPD obstruction. Materials and methods: In total, 160 patients who underwent initial MS placement for MBO were enrolled. Eighty-two patients underwent ES immediately prior to MS placement, whereas 78 underwent MS placement without ES. An inverse probability of treatment weighting method was adopted to adjust the differences of the patients' characteristics. The primary outcome was the incidence of PEP. The secondary outcomes included the incidence of other adverse events (bleeding, cholangitis, perforation and stent dislocation) and time to recurrent biliary obstruction. Results: The incidence of PEP was 26.8% in the ES and 23.1% in the non-ES (unadjusted odds ratio [OR] [95%CI]: 1.22, [0.60–2.51], adjusted OR [95%CI]: 1.23, [0.53–2.81], p = .63). Logistic-regression analysis revealed no factors that could be attributed to the occurrence of PEP. The incidence of other adverse events was not different between the groups. The median time to recurrent biliary obstruction was 131 (2–465) days and 200 (4–864) days in the ES and non-ES, respectively ( p = .215). Conclusions: ES prior to MS placement for patients with distal MBO without MPD obstruction does not reduce the incidence of PEP.